Novel Medications to Treat Addictive Disorders - Montoya, Iván D. (2008)
Recent discoveries about the effects of drugs of abuse on the brain and the mechanisms of their addictions; new chemical compounds, including immunotherapies; and new actions of available medications are offering many opportunities for the discovery and development of novel medications to treat addictive disorders. Furthermore, advancements in the understanding of the genetic and epigenetic basis of drug addiction and the pharmacogenetics of the safety and/or efficacy of the medications are providing opportunities for more individualized pharmacotherapy approaches. Although multiple medications have been investigated for treating addictions, only a handful have shown acceptable safety and efficacy and are approved by the US Food and Drug Administration. This article reviews the current medications that are medically safe and have shown promising results for treating opioid, cocaine, methamphetamine, and cannabis addictions.